Diffractive inelastic scattering of 6Li nuclei by 12C, 28Si nuclei - V. I. Kovalchuk (Ядерна фізика та енергетика)
Method of differential cross sections calculation has been proposed for inelastic diffractive scattering of clus-tered nuclei by even-even nuclei with excitation of low-lying collective states. The method satisfactorily de-scribes the experimental angular distributions of inelastic scattering cross sections of 6Li nuclei by 12C and 28Si nuclei with the excitation of 2+ states (4,44 and 1,78 MeV, respectively).